Anti-Corruption Education from the Perspective of Islamic Boarding School Education - Budiono, Budiono (Jurnal Paradigma, 2024)
Islamic boarding schools as religious institutions can be part of a good anti-corruption movement. However, its effectiveness may still be questioned. In Islamic boarding schools, for example, the kiai as the patron of the community can be used as pressure for the bureaucracy to reduce corrupt practices. However, what the kiai do can only be done within the boundaries of a cultural movement. That is, they can make moral appeals so that people avoid corrupt behavior.